Problems Concerning the Definition and Elements of the “Nominee” Offence under the Foreign Business Act B.E. 2542 (1999) - Chaowachart, Prungsak (Rajapark Journal, 2026)
This research aimed to: 1) analyze the problem of defining a “nominee” under the Foreign Business Act B.E. 2542 (1999); 2) analyze the constitutive elements of the offenses under Sections 36 and 37, including both actus reus and mens rea; 3) identify the gap between the “nominee shareholding test” and the “control test” and propose legislative measures to close it; and 4) propose reform pathways consistent with the Financial Action Task Force (FATF) Beneficial Ownership standards and Thailand’s international obligations. The study employs doctrinal legal research, supplemented by comparative references and contextual data, in a manner consistent with the methodology articulated by Hutchinson and Duncan (2012). Primary sources include the relevant statutes, Supreme Court judgments, and authoritative academic commentaries. The analysis is framed by Responsive Regulation theory (Ayres & Braithwaite, 1992) and the FATF Beneficial Ownership standards under Recommendations 24 and 25. The findings reveal: 1) the Act provides no direct definition of “nominee,” creating enforcement uncertainty; 2) the definition of “foreigner” in Section 4 (3)–(4) relies solely on a quantitative shareholding test and fails to capture indirect control through contracts, preference shares, or convertible instruments; 3) the elements of Sections 36 and 37 are open-textured and impose heavy evidentiary burdens regarding specific intent; and 4) the Thai framework is misaligned with FATF Recommendations 24 and 25, as revised in March 2022 and February 2023 respectively. The article recommends adding statutory definitions of “nominee” and “Ultimate Beneficial Owner”; supplementing the shareholding test with a “control” criterion; integrating existing UBO disclosure regimes under the AML Act, the SEC, and the Department of Business Development into a centralized registry; and classifying Sections 36 and 37 as predicate offenses under the Anti-Money Laundering Act. Reform must remain consistent with Thailand’s international commitments and constitutional principles.